ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DI KABUPATEN/KOTA PROVINSI BALI - Visera Abimanyu, Pande Made; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The objectives of this study are (1) to analyze the effect of population, government expenditure, and length of stay of tourists simultaneously on local revenue in the Regency / City of Bali Province, (2) to partially analyze the effect of population size, government expenditure, and length of stay of tourists. to the local revenue in the Regency / City of Bali Province, (3) to analyze the variables that have the most dominant influence on the local revenue in the regencies / cities of Bali Province. The data used are secondary data, with 45 observation points. The analysis technique used is multiple linear regression analysis. The results showed that (1) total population, government expenditure, and length of stay of tourists simultaneously had a significant effect on local revenue in the Regency / City of Bali Province (2) the population had a negative and insignificant effect on local revenue in the Regency / City Province. Bali (3) partially government spending has a positive and significant effect on local revenue in the Regency / City of Bali Province, (4) the length of stay of tourists partially has a positive and significant effect on local revenue in the Regency / City of Bali Province, (5) expenditure the government has the most dominant influence on local revenue in the Regency / City of Bali Province Keywords: Local Revenue, Population, Government Expenditure, Length of Stay of Tourists